2020
DOI: 10.1161/circulationaha.119.044440
|View full text |Cite
|
Sign up to set email alerts
|

Reduce-It Usa

Abstract: Background: Some trials have found that patients from the United States derive less benefit than patients enrolled outside the United States. This prespecified REDUCE-IT (Reduction of Cardiovascular Events with Icosapent Ethyl - Intervention Trial) subgroup analysis was conducted to determine the degree of benefit of icosapent ethyl in the United States. Methods: REDUCE-IT randomized 8179 statin-treated patients with qualifying triglycerides ≥135 and &l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
41
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 118 publications
(48 citation statements)
references
References 32 publications
5
41
0
2
Order By: Relevance
“…1 However, recently, the REDUCE-IT trial of a 4 g daily dose of icosapent ethyl (a purified form of EPA) among participants with high triglycerides reported a highly statistically significant 25% proportional reduction in various cardiovascular outcomes. 2 The results in both low and high dose large trials are consistent with a pro rata to dose reduction in coronary heart disease events of 7-8% per 1 g EPA+DHA supplementation. 1,2 However, in REDUCE-IT, 2 supplementation was also associated with a nominally statistically significant (without adjustment for multiple comparisons) approximate 50% increase in hospitalisation for atrial fibrillation (AF) or flutter.…”
supporting
confidence: 59%
“…1 However, recently, the REDUCE-IT trial of a 4 g daily dose of icosapent ethyl (a purified form of EPA) among participants with high triglycerides reported a highly statistically significant 25% proportional reduction in various cardiovascular outcomes. 2 The results in both low and high dose large trials are consistent with a pro rata to dose reduction in coronary heart disease events of 7-8% per 1 g EPA+DHA supplementation. 1,2 However, in REDUCE-IT, 2 supplementation was also associated with a nominally statistically significant (without adjustment for multiple comparisons) approximate 50% increase in hospitalisation for atrial fibrillation (AF) or flutter.…”
supporting
confidence: 59%
“…Whereas the replacement of SFA in the diet with MUFA increased CV events in some studies [74], other studies showed reduction [190] or no change [56,191] in CV events. As already described, one plausible The hazard ratios and 95% CI in the US and non-US population for the primary efficacy end point in REDUCE-IT study [186].…”
Section: Monounsaturated Fatmentioning
confidence: 95%
“…Recently, a subgroup analysis of REDUCE-IT study was conducted to determine the degree of benefit of EPA in the 3146 patients in the United States [186]. As shown in Figure 13, the US subgroup in REDUCE-IT demonstrated more robust risk reduction.…”
Section: Role Of Epa In Management Of CV Disease In the Futurementioning
confidence: 99%
“…The REDUCE-IT, a blinded RCT, also demonstrated that 4 g/day purified EPA reduced cardiovascular events: a composite of cardiovascular death, nonfatal myocardial infarction, nonfatal stroke, coronary revascularization and unstable angina for EPA vs. placebo was 17.2% vs. 22.0% [22,24]. However, the cardiovascular risk reduction was not associated with attainment of more normal triglyceride levels in REDUCE-IT [22].…”
Section: Effect Of Highly Purified Epa On Cardiovascular Diseasementioning
confidence: 97%
“…In the Reduction of Cardiovascular Events with Icosapent Ethyl-Intervention Trial (REDUCE-IT) and the Japan EPA Lipid Intervention Study (JELIS) using highly purified EPA, EPA significantly reduced the risk of cardiovascular events [22][23][24]. However, the effect of EPA on arterial calcification in a clinical situation is not established.…”
Section: Introductionmentioning
confidence: 99%